Prepapillary vascular loop in a girl with ventricular septal defect – case report - Isjanovski, Igor; Stefan Pandilov (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2024)
A prepapillary vascular loop is a congenital variant of normal retinal vessels that is present on and/or around the optic disc. It is a rare vascular entity, with a prevalence of 1:2000 to 1:9000 eyes. The purpose of this paper is to describe a case of a 10-year-old girl in whom a unilateral prepapillary vascular loop was observed during a routine ophthalmological examination. Because of the anamnestic data of congenital heart anomaly we performed a literature search of data available in several major medically relevant databases, but we did not come across another case where correlation of these two conditions was made. Considering that, this is the first case, known to us, where the following are present in the same patient: prepapillary vascular loop, eyelid ptosis and ventricular septal defect. A larger number of such patients is needed to draw a conclusion whether it is a systemic syndrome or a coincidental simultaneous presentation of multiple entities in the same patient.
Keywords: optic nerve; papilla; congenital abnormality; vascular loop